Holocene hydroclimate changes on the north‐eastern Tibetan Plateau inferred from geochemical records in Lake Gyaring. (12th October 2021) - Ning, Dongliang; Jiang, Qingfeng; Ji, Ming; Xu, Yuchen; Kuai, Xiang; Ge, Ying; Zhao, Wenwei
ABSTRACT: The north‐eastern Tibetan Plateau (TP) is an ideal region for understanding the interaction between the Asian Summer Monsoon (ASM) and the Westerlies. Here we present a high‐resolution elemental record from Lake Gyaring in the source region of the Yellow River to investigate the paleo‐hydroclimate changes over the past 10 ka. Our results show that lithogenic elements (Ti, Rb, Mn, Ti, Zn and Ni) increased while carbonate‐related elements (Ca, Sr and Mg) decreased up the core sediments, indicating that the effective moisture on the north‐eastern TP has steadily increased throughout the Holocene. This inference is also supported by the gradual augmentation and diminution of Rb/Sr and Ca/(Ti + Fe + Al) ratios, respectively. The persistent wetting trend on the north‐eastern TP inferred from our study disagrees with the Holocene pattern of the ASM but corresponds well with that of the Westerlies. This implies that the strengthening Westerlies since the Holocene might have played a more important role than monsoon circulation in controlling the hydroclimate changes on the north‐eastern TP. However, the significant increase in the mid‐Holocene might be related to the combined effects of the strengthened ASM and Westerlies. Ultimately, Northern Hemisphere solar insolation and the substantial remnant of ice sheets might have controlled Holocene moisture availability on the north‐eastern TP through their influence on the intensity of the Westerlies and ASM as well as Atlantic Ocean sea surface temperatures.